Investigation of Hydraulic Performance of the Stairs Transitional Field (SEDEX PROFILE) on the Upper Slope Step overflow (Case Study: Jahve dam) - Kazem Dalili khanghah; Mohammadreza Kavianpuor (مهندسی و مدیریت ساخت, 2017)
With the advancement of roller concrete dams (RCC) technology and stack overflow compatibility with these types of dams, stepped overflows have been used more than ever. Due to the complexity of hydraulic steppe overflows, many laboratory models have been developed and tested to achieve empirical relationships governing the flow of these types of overflows. To improve laboratory methods, we can use computational fluid dynamics (CFD) and numerical simulation based on it. In this paper, using the 3D-FLOW software (computational software based on computational fluid dynamics), flow behavior on the overflow of the Javew dam in two states with and without stepwise transitional area was investigated and by comparing the flow behavior in these two modes It was found that the CEDEX profile showed better performance than the no-transition mode and prevented water jumps on the stairs.